Vaccines are underused in pregnancy: what about knowledge, attitudes and practices of providers? - Riccò, Matteo; Vezzosi, Luigi; Balzarini, Federica; Gualerzi, Giovanni; Ranzieri, Silvia; Khamisy-Farah, Rola; Bragazzi, Nicola Luigi (Acta Biomedica Atenei Parmensis, 2020)
Introduction. To investigate actual knowledge of official recommendations towards seasonal influenza (SID), and Tetanus-diphtheria acellular-pertussis (Tdap) vaccines in obstetrics/gynecologists (OBGYN). Methods. PubMed and EMBASE databases were searched. A meta-analysis was performed to calculate odds ratio (OR) and 95% confidence interval (CI) among case controls, cross-sectional studies, either questionnaire or laboratory exams based. Results. A total of 6 studies met inclusion criteria, including 1323 OBGYN from 5 different countries. Overall, around 99% of sampled professionals were aware that official recommendations towards SID in pregnancy do exist, compared to 92% for Tdap, with significant heterogeneity (I2 > 95%, p < 0.001). Concerns about vaccine safety was reported by 10% of respondents for Tdap, and by 6.0% for SID, but again available studies were substantially heterogenous (I2 = 86.7% and 86.0%, p < 0.001). Eventually, 93% of respondents actively recommended SID in pregnancy, compared to 88% for Tdap (I2 98.8% and I2 95.9%, respectively p < 0.001). The evidence of significant publication bias was initially subjectively identified from the funnel plot, and then objectively confirmed through the regression test for all analyses. Conclusions. These results suggest an appropriated understanding of official recommendation among sampled OBGYN, with high shares of professionals actively promoting vaccination practices among their patients. Despite the high heterogeneity and the significant publication bias we identified, our results also hint towards extensive knowledge gaps of OBGYN, and particularly regarding unmotivated concerns about vaccine safety. As a consequence, appropriate information and formation campaigns should be appropriately tailored.